Costs for the Development of a Virtual University - Turoff, Murray (Online Learning, 1997)
This paper is an update of one that the author published in 1982. It deals with the costs and effort required to set up a first class academic program for 2000 students that is made up of students and faculty scattered around the world. The establishment of such a University would cost less than the addition of a single classroom building on a physical college campus (approximately $15 million US).